PENGARUH STORE ATMOSPHERE, KUALITAS LAYANAN, DAN FASILITAS PENDUKUNG TERHAAP PREFERENSI MASYARAKAT DALAM MEMILIH KAFE KOPILABORASI SEBAGAI TEMPAT BEKERJA DAN BERSOSIALISASI DI SURABAYA - Palupi , Yaladriya Raras; widodo, Agus purbo; jondar, aloysius (JEB17 : Jurnal Ekonomi dan Bisnis, 2025)
This study aims to analyze the influence of store atmosphere, service quality, and supporting facilities on people's preferences in choosing Kopilaborasi Cafe in Surabaya as a place to work and socialize. The phenomenon of the increasing role of cafes as alternative spaces for productivity and social interaction among urban communities is the main background of this study. The method used in this study is a quantitative method with a survey approach. Data collection techniques were carried out by distributing closed questionnaires to122 respondents who were active users of cafes for work or socializing activities. Samples were taken purposively, and data were analyzed using multiple linear regression to determine the effect of each independent variable, namely store atmosphere (X₁), service quality (X₂), and supporting facilities (X₃), on the dependent variable, namely consumer preferences (Y). The results of this study are expected to provide theoretical contributions to the study of consumer behavior as well as practical implications for cafe business actors in designing experiential marketing strategies that are relevant to the needs of urban communities in Surabaya.